Thinking the unthinkable : coming to grips with Islamic state - James M. Dorsey (2015)
Despite a year- long campaign of air strikes and ground attacks which incurred heavy losses Islamic State (IS) shows continued resilience. The US-led coalition’s alliances with militant groups and IS’ durability raise the spectre of jihadist groups becoming a more permanent fixture in the Middle East.